Identification of PROK2 gene polymorphisms as predictors of methamphetamine use disorder risk and indicators of craving scale in the Chinese Han population - Jiang, Zhao; Zhang, Tianxiao; Han, Wei; Xiao, Jing; Zhang, Wenpei; Wang, Xiaochen; Liu, Jianing; Yang, Ying; Yang, Congying; Guan, Fanglin; Li, Tao; Rice, John P. (Frontiers in Pharmacology, 2023)
Background: Methamphetamine use disorder (MUD) has become a global problem due to the highly addictive nature of methamphetamine. Earlier research have demonstrated that PROK2 functions as a compensatory and protective response against neurotoxic stress by stimulating astrocyte reactivity. The aim of our study was to evaluate the correlation between the PROK2 gene and both MUD risk susceptibility and craving scale in the Chinese Han population.Methods: A total of 5,282 participants (1,796 MUD patients and 3,486 controls) were recruited. Seven tag SNPs of the PROK2 gene were chosen and genotyped in the samples. Genetic association analyses were performed to capture the significant SNPs.To investigate the relationship between PROK2 levels and craving scores with the associated-SNP genotypes, we conducted a linear model.Results: SNP rs75433452 was significantly linked with MUD risk (P-value=1.54× 10 -8 ), with the A allele being positively correlated with an increased risk of MUD. Moreover, the average serum level of PROK2 decreased when more copies of the A allele were presented in both MUD patients (P-value=4.57 × 10 -6 ) and controls (P-value=1.13×10 -5 ). Furthermore, the genotypes of SNP rs75433452 were strongly correlated with the craving scores in MUD patients (P-value=4.05×10 -4 ).Our study identified a significant association signal of the PROK2 gene with MUD risk susceptibility and methamphetamine craving scores in the Chinese Han population, providing potential valuable insights into the underlying mechanisms of METH dependence.